Cardiomyocyte‐Driven Actuation in Biohybrid Microcylinders. (24th June 2015) - Yoon, Jaewon; Eyster, Tom W.; Misra, Asish C.; Lahann, Joerg
<x xml:space="preserve">Abstract</x> Biohybrid microcylinders are fabricated using electrohydrodynamic cojetting followed by a surface chemistry approach to maximize cell‐adhesive characteristics. As proper cell alignment and mechanical stiffness are important components of bioactuator design, spatial cell selectivity and stress/strain properties of microcylinders are characterized to demonstrate their capability of response to rat cardiomyocyte contraction. These microcylinders can find applications in a host of micromechanical systems.